Geologia, geoquímica e petrologia magnética dos granitoides Arqueanos da Porção Nordeste de Água Azul do Norte - Província Carajás - GABRIEL, Eleilson Oliveira (Universidade Federal do Pará, 2019)
Petrographic and geochemical studies of Archean granitoids under taken during the geological mapping of the NE portion of the Água Azul do Norte area - Carajás Province, allowed the identification of new units that were previously inserted into the Xingu Complex. The granitoids individualized are: (i) the Água Azul and Água Limpa granodiorites, which are high-Mg granitoids, similar geochemical to the Archaean sanukitoid occurring in other areas of the Carajás Province as well as in the Karelian and Superior provinces; (ii) a pluton of Trondhjemite with affinity to the classical TTG, not identified in previous studies in this area; (iii) three bodies of Leucogranodiorites and one of Leucogranite all of them with calc-alkaline signature and geochemically similar to the leucogranodiorites-granites of the Guarantã Suite of the Rio Maria Domain. These Archaean granitoid are intrusive in the supracrustal sequences of the Sapucaia Group and occur as deformed bodies, generally elongated along EW. The Água Azul and Água Limpa granodiorites are composed essentially of (epidote)- amphibole-biotite granodiorite and tonalite with (muscovite)-(epidote)-biotite granodiorite and monzogranites. Biotite trondhjemites and subordinate biotite tonalites are the rock varieties identified in the Trondhjemite pluton. The occurrences of Leucogranodiorites consist of biotite granodiorites, and the Leucogranite body is composed of biotite monzogranites. The Água Azul and Água Limpa granodiorites are predominantly metaluminous and exhibit higher values of Mg#, Cr and Ni when compared to the calc-alkaline series from continental margins and Archean TTG suites and leucogranodiorites of the Rio Maria Domain. The magnetic susceptibility (MS) values obtained in the rocks of these two bodies are relatively low (average 17.54 x10-4 SIv for the Água Limpa and average 4.19 x10-4 SIv for the Água Azul granodiorites). Magnetite and hematite are the more common opaque minerals and ilmenite is absent in these rocks. The magnetite crystals are more abundant and larger in the Água Limpa Granodiorite compared to the Água Azul Granodiorite, justifying the highest values of MS found in this pluton. In general there is a tendency of increasing of MS values in the sense of the less evolved facies (amphibole tonalite + amphibole granodiorite) to more evolved facies (biotite granodiorite + biotite monzogranite). The more magnetic samples are related to magnetite formed during deformational processes in shear zones. Because of the geochemical and mineralogical similarities between these rocks and sanukitoids of Rio Maria, it is assumed conditions of the fO2 between HM and FMQ buffers for granitoids of the Água Azul do Norte.